Independent recombination events between the duplicated human alpha globin genes; implications for their concerted evolution. - Higgs, D; Hill, A; Bowden, D; Weatherall, D; Clegg, J (1984)
We have examined the molecular structure of the human alpha globin gene complex from individuals with a common form of alpha thalassaemia in which one of the duplicated pair of alpha genes (alpha alpha) has been deleted (-alpha 3-7). Restriction mapping and DNA sequence analysis of the mutants indicate that different -alpha 3.7 chromosomes are the result of at least three independent events. In each case the genetic crossover has occurred within a region of complete homology between the alpha 1 and alpha 2 genes. Since the -alpha chromosomes may reflect the processes of crossover fixation and gene conversion between the two genes, their structures may provide some insight into the mechanism by which the concerted evolution of the human alpha globin genes occurs.